ANALISIS RESPONS SISWA TERHADAP PENGGUNAAN GOOGLE SITES SEBAGAI MEDIA PEMBELAJARAN PADA MATERI PERMINTAAN, PENAWARAN, DAN HARGA KESEIMBANGAN DI KELAS X-5 SMAN 1 MEDAN - Samuel Revaldo Jeverson Siboro; Bona Vintura Suyana Pandiangan; Josua Pane; Excaudia Mazmuris Siringoringo; Evi Syuriani Harahap (STKIP Subang, 2026)
This study aims to analyze student responses to the use of Google Sites as a learning medium for demand, supply, and equilibrium price material in class X-5 SMAN 1 Medan. The research employed a qualitative descriptive approach with 13 students as research subjects. Data were collected through in-depth interviews using four structured questions covering aspects of comprehension ease, visual display perception, learning engagement level, and conceptual understanding in real-life contexts. The results indicate that 61.5% of students found Google Sites helpful or very helpful in understanding economics material, 84.6% gave positive assessments of Google Sites' visual display, 69.2% found learning through Google Sites more engaging than conventional instruction, and 69.2% reported better understanding of demand, supply, and equilibrium price concepts in real-life contexts. However, 30.8% of students still considered the teacher's lecture method more effective due to direct interaction and instant feedback. These findings suggest that Google Sites holds significant potential as a digital learning medium, but its effectiveness would be more optimal when synergistically integrated with conventional instructional methods. The findings align with the Multimedia Learning Theory (Mayer, 2009), Constructivism Theory, and previous research on the effectiveness of technology-based learning media.